The making of a philosopher : my journey through twentieth-century philosophy - McGinn, Colin, 1950- (HarperCollins, 2002)
"Part memoir, part study, The Making of a Philosopher is the self-portrait of a deeply intelligent mind as it develops over a life lived on both sides of the Atlantic.".